Analisis rasio terhadap kinerja keuangan pada PT Supra Boga Lestari Tbk - Tewang, Maria Farida; Harahap, Dea Arme Tiara (Journal of Economics, Business, Accounting and Management, 2024)
This study was conducted to determine the financial performance of PT Supra Boga Lestari Tbk as seen from the analysis of financial ratios for 2019-2022. The ratios to be analyzed are solvency ratios including debt to asset ratio and debt to equity ratio. Liquidity ratios include current ratio, quick ratio and cash ratio and profitability ratios include net profit margin, return on asset ratio and return on equity ratio. The research conducted is quantitative descriptive research by collecting, describing and describing the data as it is. The data source in this study is secondary data taken from the financial statements of PT Supra Boga Lestari Tbk published on the Indonesia Stock Exchange website. Based on the results of the ratio analysis of the financial statements of PT Supra Boga Lestari Tbk, it is known that the solvency ratio in 2019-2022 seen from the average value of the debt to asset ratio and debt to equity ratio is in poor condition. The liquidity ratio in 2019-2022 seen from the average value of the current ratio, quick ratio and cash ratio is in poor condition, as well as the profitability ratio seen from the average value of the net profit margin ratio, return on asset ratio and return on equity ratio in poor condition. from the results of the analysis of the financial ratios of PT Supra Boga Lestari Tbk from 2019-2022 it can be concluded that the company's financial performance from the solvency ratio shows that the company has a very high debt burden. The liquidity ratio shows that the company is less able to pay off its short-term debt, while the profitability ratio shows that the company's capital and assets have not been used optimally in making a profit.